Deep learning of contagion dynamics on complex networks - Charles Murphy (Nature Portfolio, 2021)
Prediction of contagion dynamics is of relevance for epidemic and social complex networks. Murphy et al. propose a data-driven approach based on deep learning which allows to learn mechanisms governing network dynamics and make predictions beyond the training data for arbitrary network structures.